Monitoring the eutrophication using Landsat 8 in the Boka Kotorska Bay - Đurović, Blažo; Đurović, Igor; Joksimović, Aleksandar, biolog; Crnojević, Vladimir; Đukanović, Slobodan; Pestorić, Branka (2018)
This study proposes a methodology for monitoring concentrations of chlorophyll a (Chl-a) and the state of eutrophics in small bays or in the immediate vicinity of the coast. This kind of monitoring is of interest since such areas have not been addressed well using the usual satellite methods (such as MODIS) due to inadequate spatial resolution. We present an estimation approach for Chl-a concentration based on Landsat 8 (L8) satellite images using the ground truth (GT) data for the day of overflight. Additionally, two classifiers (daily and yearly) of the state of eutrophication, that use the Chl-a estimated values, are presented. The accuracy of the proposed method is evaluated using the leave-one-out cross validation, and it is within limits theoretically expected of an L8-based approach. The results from the classifiers are compared with the GT data and it is shown that daily classifier is able to classify the area of interest with an incidence of false positives less than 2%.
Ova studija predlaže metodologiju za nadgledanje koncentracija klorofila-a i eutrofičnog stanja u malim zalivima ili u blizini obale. Ova vrsta nadgledanja je zanimljiva jer uobičajena satelitska metodologija, bazirana na MODIS satelitu, nije funkcionalna u ovim oblastima zbog nedovoljne prostorne rezolucije senzora. U ovom radu je predstavljen pristup procjeni koncentracija klorofila-a baziran na Landsat 8 satelitskim snimcima i mjerenjima koncentracije obavljenim na određenim lokacijama na dan prelijetanja satelita. Dodatno, dva klasifikatora stanja (dnevni i godišnji) eutrofikacije, koji koriste određene koncentracije, su također prikazani. Preciznost predloženih metoda je procijenjena koristeći „leave-one-out“ unakrsnu validaciju, te rezultati pokazuju da je preciznost unutar teoretskih limita metoda baziranih na Ladsat 8 satelitu. Rezultati klasifikatora upoređeni su sa mjerenjima na terenu i pokazuju da je dnevni klasifikator u mogućnosti da klasificira oblast od interesa sa manje of 2% pogreški.
Bibliografija: str. 29-32.
Summary ; Sažetak.
Keywords: Landsat 8; Klorofil α -- Eutrofikacija -- Satelitske snimke